Sparking Student Synapses, Grades 9-12: Think Critically and Accelerate Learning. - Allen, Richard, 1957 September 28- (Corwin, A SAGE Publications Company, 2011)
Today's students must be more than good test takers. They must be able to collaborate, innovate, and think critically to solve real-world problems. As content demands increase, how can teachers make time to teach these advanced skills? "Sparking Student Synapses, Grades 9-12" describes how master teacher Nigel Scozzi used Rich Allen's Green Light strategies to teach content in a memorable and efficient way. Backed by research, this practical guide provides secondary teachers with tried and trusted lesson plans, in multiple subject that: (1) Engage students; (2) Accelerate learning; (3) Encourage critical thinking; and (4) Improve test results. When you apply the book's effective strategies, your students will learn to make appropriate judgments based on the evidence available, understand relationships between ideas, evaluate content validity, and reflect upon their values. Changing the way you teach may be daunting, but the results are worth it--improved student engagement and behavior, better test results, and a rewarding reminder of why you became a teacher!